2015
DOI: 10.1039/c4tb01880j
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular assembly of crosslinkable monomers for degradable and fluorescent polymer nanoparticles

Abstract: Intermolecular B-N coordination has been recognized as a promising driving force for molecular self-organization. However, direct utilization of this intermolecular interaction as building bridge for the supramolecular self-assembly of chemical functionalities to form nano-sized architectures remains a daunting challenge. Here, we outline a multiple intermolecular B-N coordination based supramolecular system, where small boronate molecules can be brought together in solution to form nanoparticles with controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…A supramolecular approach is developed to fabricate inorganic@BP (including nanocrystal@BP) core–shell particles. Condensation reaction between a catechol monomer and a boronic monomer with multiple functionalities on the surface of inorganic nanoparticles affords BP cross-linked networks, which generates two types of supramolecular interactions: first, a strong interaction between BP and nanocrystal contributed by the high binding affinity of catechol moiety to inorganic surface; second, a relatively weaker B–N dative bonding among BP chains, which is capable of organizing polymers into well-defined assemblies as demonstrated in our previous work. With this elegantly designed supramolecular approach, we are able to precisely control and predict the BP shell thickness on the surface of inorganic nanoparticles with various components, sizes, and shapes.…”
Section: Introductionmentioning
confidence: 99%
“…A supramolecular approach is developed to fabricate inorganic@BP (including nanocrystal@BP) core–shell particles. Condensation reaction between a catechol monomer and a boronic monomer with multiple functionalities on the surface of inorganic nanoparticles affords BP cross-linked networks, which generates two types of supramolecular interactions: first, a strong interaction between BP and nanocrystal contributed by the high binding affinity of catechol moiety to inorganic surface; second, a relatively weaker B–N dative bonding among BP chains, which is capable of organizing polymers into well-defined assemblies as demonstrated in our previous work. With this elegantly designed supramolecular approach, we are able to precisely control and predict the BP shell thickness on the surface of inorganic nanoparticles with various components, sizes, and shapes.…”
Section: Introductionmentioning
confidence: 99%
“…Instead of linking two different molecular building blocks via dative B–N bonds, it is also possible to employ boronate esters which feature N-donor ligands as side chains. Self-aggregation can then lead to the formation of molecularly defined and polymeric supramolecular structures. …”
Section: Introductionmentioning
confidence: 99%
“…We have also found that intermolecular B-N dative bond can be formed among small molecules [40]. A planar boronate ester (BCe), containing two imine moieties, a boronate ester group and two polymerizable carbon-carbon double bonds, has been created by the condensation reaction between a boronic acid molecule (BM) and a catechol molecule (CM) (Figure 33).…”
Section: Sheepwash and Coworkers [38] Utilizedmentioning
confidence: 99%